(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article examines the level of study in the field of history and literature of one of the most important events in Kazakh history – the Zheltoksan uprising. Of the uprisings that took place in the Cossack steppes, the most important is the Zheltoksan uprising. Therefore, a review of all scientific papers on this topic is being conducted. The defended dissertations of Kazakhstani and foreign scientists on this topic will be considered, which will determine the scientific specifics of the research. Based on this, the small number of studies is proved. It was found that none of the above-mentioned scientific papers conducted exhaustive studies of the artistic worlds associated with the historical event of the historical era. Short stories, novellas, novels and dramatic works based on facts from the history of Zheltokson still remain not reasoned and not amenable to analysis. The necessity of scientific research to reveal the Zheltokson realities is substantiated. The necessity of scientific research to reveal the Zheltokson realities is substantiated.